MARKETING STRATEGY IN BUILDING BRAND AWARENESS (Qualitative Study On Instagram Account @localprideindonesian) - Sania Nerissa; Juwito (Universitas Islam Balitar, 2021)
Brand awareness or brand awareness is one way to measure marketing effectiveness as measured by the ability of customers to recognize and remember names, images and signs associated with certain brands. According to Charles in Atmoko (2018), strategy is a concept of how companies and institutions organize themselves and all activities related to them so that the business they run can succeed in competition. The data sources in this study were 4 informants, 1 Co-founder of the @localprideindonesian Instagram account and 3 business people who had used paid promotional services on the @localprideindonesian Instagram account. The data technique used is the depth interview technique. The results of the study show how the @localprideindonesian Instagram account marketing strategy in building brand awareness. This is influenced by the informant's internal factors, where the informant knows that Instagram social media can build brand awareness by optimizing marketing strategies, so that activities become more effective.